Integrating Ahlul Halli Wal Aqdi Principles into Legislative and Voter Qualifications in Indonesia's Electoral - Sadzali, Ahmad; M. Yasin al Arif (Universitas Islam Negeri Raden Intan Lampung, 2026)
Democracy in Indonesia still faces challenges related to the quality of legislative representatives and voter eligibility requirements, which remain largely administrative in nature. This study seeks to adopt the perspective of the Ahlu Halli wal Aqdi concept to examine and address this issue. There have been many studies that compare the concept of Ahlul Halli wal Aqdi with the democratic system without reaching the level of conceptual internalization. This study attempts to answer the following questions: (1) How is the value of the Ahlul Halli wal Aqdi concept actualized in the context of the qualification requirements for legislative candidates and voter qualifications?; and (2) What ideas emerge from the actualization of the value of the Ahlul Halli wal Aqdi concept for the representative democratic system in Indonesia? This normative legal research employs conceptual and legislative approaches, using primary legal materials derived from various election-related laws and regulations. The actualization results show that the Ahlul Halli wal Aqdi concept prioritizes quality in both input and output. The ideas that emerge from this actualization are: (a) Building a political paradigm based on quality; (b) Re-evaluating the political education curriculum; (c) Strengthening political education by state institutions; (d) Improving the quality of prospective members of representative institutions; and (e) strengthening the independence of members of representative institutions. The implications of this study call for broader research on the actualization of classical Islamic concepts, as well as greater openness and commitment from the state to pursue more substantial electoral law reforms